How do Entrepreneurial Competence and Personal Independence affect Micro Business Success in Makassar City? - Sitti Hasbiah; Ilma Wulansari Hasdiansa (Pinisi Journal of Entrepreneurship Review, 2023)
This study aims to determine the effect of Entrepreneurial Competence and Personal Independence on Micro Business Success in Makassar City. The research is categorized as quantitative descriptive research with a population of 230 micro businesses located in Makassar City. Data collection in this study was carried out using observation, questionnaire, interview and documentation techniques. The analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that entrepreneurial competence and personal independence together have a positive and significant effect on the success of micro businesses in Makassar City. This can be seen from the data analysis obtained the amount of entrepreneurial competence and personal independence on business success, and hypothesis testing has been carried out (t test). The results of the analysis obtained that the variables of entrepreneurial competence (X1) and personal independence (X2) have a positive relationship to business success. So it can be said that there is a positive and significant influence between entrepreneurial competence and personal independence on the success of micro businesses in Makassar City.